The diversity of sugarcane production systems and dynamics in the family agroindustry: a multiple case study in the state of Paraná, Brazil (Research, Society and Development, 2023)
The rural environment, due to its diversity and cultural richness, represents a place of countless possibilities. In this sense, sugarcane as a base element to produce derivatives in family agro-industries is a factor of great relevance for their maintenance and as an influencing element in the construction of markets. In view of this, this article investigates the dynamics of sugarcane derivatives in the context of family agroindustry, which organize different systems and articulate production and marketing in three municipalities in the state of Paraná, southern Brazil. This research is cross-sectional and was developed from the selection of multiple cases in the municipalities of Capanema, Guaraniaçu and Marechal Cândido Rondon. Data collection was performed by unsystematic observation in loco and semi-structured questionnaires. This article, therefore, presents notions about the interviewees' satisfaction with the productive practices of agribusinesses, as a means of autonomy, preservation of cultural practices and family maintenance. In addition, it was found that the diversity of systems indicates improvements in the flow of sales, on quality of life of their families and offering greater visibility for both sugarcane derivatives and family agro-industries in the region. The choice for the cultivation of sugarcane is related beyond the mercantile logic, with aspects of affinity and productive diversification. However, this study provides evidence about a still little explored market, which needs scale expansion and technological improvements in family agribusinesses.